Optimization of Non-Uniform Perforation Parameters for Multi-Cluster Fracturing - Qingdong Zeng; Wenzheng Liu; Jun Yao (Energies, 2022)
Stress shadowing affects the simultaneous propagation of fractures from multiple perforation clusters. Employing uniform perforation parameters for all clusters cause the unbalanced growth of fractures, which arouses the demand of optimizing non-uniform perforation parameters. An optimization workflow combining a fracture propagation model and the particle swarm optimization method (PSO) is proposed for multi-cluster fracturing in this study. The fracture model considers the coupling of rock deformation and fluid flow along the wellbore and fractures, and it is solved by using the Newton iteration method. The optimization is performed by taking the variance of multiple fracture lengths as fitness value function in the frame of the PSO method. Numerical results show that using the same spacings and perforation parameters for all clusters is detrimental to the balanced growth of multiple fractures. The variance of fracture lengths drops greatly through optimization of cluster spacings and perforation number/diameter. Properly increasing the spacing and perforation number/diameter for the middle clusters promotes the balanced growth of multiple fractures. This study provides an efficient optimization workflow for multi-cluster fracturing treatment in horizontal wells.